Formas de aprender a investigar en la licenciatura de enfermería - Luna Rojas, José Angel (2016)
Qualitative descriptive study whose objectives were to describe and discuss ways to learn how to research in nursing degree. The work was based on the theoretical framework of Pedro Demo (2005, 2007). The scenario was the School of Nursing and Midwifery of the National Polytechnic Institute in Mexico City, Mexico. Semistructured interview to seven students of the seventh semester of undergraduate nursing was applied. Content analysis of speeches was used. What revealed the phenomenon through three categories: 1) Space and time learning to build and rebuild, with six criteria: Observation, Reading, Interview, documented Reconstruction, Articulating theory and practice, and Transiting in virtuality. 2) Action reflective multidimensional; three criteria: dimensional analysis, dimensional analysis and dimensional analysis. 3) Humanizing learning to investigate; five criteria: Interest, Affiliation, empathy, assertiveness and sensitive dialogue. He had the final considerations that learning to research in nursing degree, is a complex process of learning, of subjective interaction between teacher and student, applicant a humanized treatment and continuous support and recursive, which requires the development of cognitive skills , social interaction, human, technical and instrumental interaction; with a close link between theory and practice of discipline; plus the ability to search for information, information analysis, academic documentary design, management of information technology and communication and learning tutoring.